Pengetahuan Penerapan Keselamatan Pasien (Patient Safety) Pada Petugas Kesehatan - Nining Sri Ningsih; Endang Marlina (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2020)
ABSTRACT Patient safety is the basis of good health services. Knowledge of health personnel in patient safety targets consists of accurate patient identification, increased effective communication, increased safety of drugs that need to be watched, certainty in the right location, procedures, and precise patient surgery, reduction in risk of infection, reduction in risk of falling patients. The purpose of this study was to determine the relationship between knowledge and the application of patient safety to health workers in the Kedaung Wetan Health Center, Tangerang City. The research method uses descriptive correlation using cross sectional approach. The population is 50 respondents. The sampling technique uses total sampling. The instrument used was a questionnaire sheet. The analysis technique above uses Univariate and Bivariate analysis. The results of the study there is a Relationship of Knowledge with the Implementation of Patient Safety in Health Officers, with the result, p value of 0.013 <0.05, it can be concluded that there is a Relationship between Knowledge and Patient Safety Implementation in Health Officers. Conclusions and Recommendations The results of the study have a Relationship between Knowledge and the Application of Patient Safety. It is recommended for health workers to further increase knowledge about the application of patient safety targets, both by attending seminars and by following the workshop continuously, so that it is expected that the application of patient safety can be applied more optimally and create safe health services and in accordance with patient safety target standards.